Contemporary telekung in Malaysia it's challenges and realities / Norzaleha Zainun, Jamiaah Abdul Holed and Zolina Mohamad - Zainun, Norzaleha; Abdul Holed, Jamiaah; Mohamad, Zolina (2017)
Fashion and trends offers an unlimited choice of how to dress to the society. This happens also in the contemporary telekung in Malaysia. Beauty is one of the elements which cannot be separated by Muslims women. The teaching in Islam about dressing among women and the understanding of the concept of aurah has positively growing up and open up the horizon in creativity in the Islamic attire. At present, fashion designers now compete among themselves to create new contemporary telekung with variety choice of colors and motif. They have created some very interesting fashion and trends in the contemporary telekung until the function and the main purpose of wearing telekung for worship to Allah turn to center of attention. This paper discusses the present situation of the contemporary telekung in Malaysia. Examples of current contemporary telekung in local market will be used as a case study.